Targeted and untargeted profiling of alkaloids in herbal extracts using online solid‐phase extraction and high‐resolution mass spectrometry (Q‐Orbitrap). (25th August 2016) - Nardin, Tiziana; Piasentier, Edi; Barnaba, Chiara; Larcher, Roberto
Abstract : The biological activity of alkaloids (ALKs) and the different content of these natural products in herbs and plants have made them an attractive field for chemical studies. A screening method automatically combining online solid‐phase purification and concentration of samples with analysis using ultra‐high performance liquid chromatography coupled with a hybrid quadrupole orbitrap mass spectrometer was developed and is reported in this paper. The proposed quantification method was validated for 35 ALKs with reference to pure analytical standards. A further 48 ALKs were identified on the basis of their accurate mass and characterised for chromatographic retention time and fragmentation profile, following their confirmation in extracts of herbs already well documented in the literature. More than 250 other untargeted ALKs were also tentatively identified using literature information, such as exact mass and isotopic pattern. The mass spectrometer operated in positive ion mode and mass spectra were acquired, with full MS‐data‐dependent MS/MS analysis (full MS–dd MS/MS) at a resolution of 140 000. The method was linear up to an ALK concentration of 1000/3000 µg l −1, with R 2 always >0.99 and limits of detection ranging between 0.04 and 10 µg l −1 . Accuracy, expressed as the recovery relative error, had a median value of 7.4%, and precision (relative standard deviation %) was generally lower than 10% throughout the quantitation range. The proposed method was then used to investigate the targeted and untargeted ALK profile of a selection of 18 alpine herbal plants, establishing that pyrrolizidine, pyrrolidine and piperidine ALKs were the most well represented. Copyright © 2016 John Wiley & Sons, Ltd.